Phenological mismatches of Myracrodruon urundeuva Allemão (Aroeira) between an anthropogenic and preserved Caatinga fragment - Maria José da Silva Filha; Bruno Ayron de Souza Aguiar; Vanessa Kelly Rodrigues de Araujo; Juliana Ramos de Andrade; Josiene Maria Falcão Fraga dos Santos; Elifábia Neves de Lima; Elcida de Lima Araújo (Acta Botânica Brasílica)
Abstract Plant phenological responses are highly sensitive to micro- and macroclimatic changes, which can be intensified by anthropogenic disturbances in the Caatinga. This study investigates the differences in the phenological timing (i.e., phenological mismatches) of vegetative and reproductive phenophases of Myracrodruon urundeuva Allemão (Aroeira) in a young and mature anthropogenic forest area within the same Caatinga fragment. We tested the effects of temperature and precipitation on the temporal variation of the phenophases. For one year, plants from a young forest area (21 years) and a mature forest area (over 90 years) were monitored monthly to record vegetative phenophases (leaf emergence, senescence, and leaf abscission) and reproductive phenophases (flowering and fruiting). We calculated the activity (presence/absence) and phenological intensity of the plants. Circular statistics were used to study phenological patterns in both forests. Compared to the mature forest, the younger forest exhibited increased leaf emergence and a prolonged period of leaf abscission. Early fruiting observed in the anthropized forest may affect its reproductive success, depending on annual precipitation patterns for the germination of its recalcitrant seeds. Decreased rainfall and higher temperatures in the Brazilian semi-arid region increase the vulnerability of this tree, potentially aggravated by anthropogenic disturbances.